Electromagnetic shielding concrete and preparation method thereof
By using microwave absorbing artificial aggregates from coal gasification slag, the dispersibility and cost issues of carbon-based additives in electromagnetic shielding concrete are addressed, achieving enhanced shielding performance and mechanical strength at lower costs.
Patent Information
- Application Number
- CN202411118989.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-15
- Publication Date
- 2025-01-03
- Estimated Expiration
- 2044-08-15
AI Technical Summary
Existing electromagnetic shielding concretes face issues with poor dispersibility and high cost of carbon-based additives like graphite and graphene, leading to limited dosage and hindered electromagnetic shielding performance, along with high production costs.
Incorporation of microwave absorbing artificial aggregates made from coal gasification slag and carbide slag, which are low-cost and evenly distributed, enhancing electromagnetic shielding without segregating, and maintaining mechanical strength.
The solution achieves improved electromagnetic shielding performance with compressive strengths of 30-48 MPa and electromagnetic shielding effectiveness of 11-48 dB across various frequencies, while reducing production costs and utilizing industrial waste.
Smart Images

Figure CN118637877B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of concrete materials, and in particular relates to electromagnetic shielding concrete and a preparation method thereof. Background Art
[0002] With the advent of the information age, the number of radio frequency devices has increased dramatically, leading to increasingly serious problems of electromagnetic pollution, electromagnetic interference and electromagnetic leakage. In response to the electromagnetic pollution, electromagnetic interference and electromagnetic leakage problems in civil buildings, communication facilities and military projects, building electromagnetic protection has gradually become a new requirement in construction. Electromagnetic shielding concrete is a functional building material developed by introducing electromagnetic shielding functional components into concrete to solve the problem of electromagnetic radiation.
[0003] In the existing technology, the absorption of electromagnetic waves by concrete is mainly increased by adding carbon-based materials such as graphite (zero-dimensional), carbon fiber (one-dimensional), and graphene (two-dimensional).
[0004] The invention patent application with publication number CN105418036A discloses an electromagnetic shielding concrete, the raw materials used of which include, by weight: 70-80 parts of binder, 10-15 parts of carbon fiber, 8-10 parts of carbon black, 5-10 parts of mica powder, 0.5-0.8 parts of rubber powder, 0.1-0.3 parts of water reducer, and 0.05-0.1 parts of defoamer; the preparation method thereof is specifically to mix the above raw materials with aggregate, add water and mix well, and then pour into a structure constructed of foam copper, and then grind and polish it after curing.
[0005] The invention patent application with publication number CN102219447A discloses an electromagnetic shielding concrete and a preparation method. An electromagnetic shielding concrete, characterized in that it includes a cementitious material, an aggregate, a fiber, a water reducer and water, wherein the cementitious material is composed of cement and an inorganic mineral admixture, and the inorganic mineral admixture is composed of at least one of fly ash and slag powder and silica fume; the aggregate is composed of coarse aggregate and fine aggregate, the coarse aggregate is ordinary stone with a particle size of 5-20mm; the fine aggregate is composed of sand, steel sand and graphite powder, and the fiber is composed of steel fiber and carbon fiber, and the proportion of each component is: water 175-180kg / m 3 Aggregate 1725~1760kg / m 3 The mass percentage of each component is: fine aggregate 35-40%, coarse aggregate 60%-65%, water-cement ratio is 0.32~0.34, the volume content of steel fiber is 0.8%-1.2% of the volume of concrete, the mass content of carbon fiber is 0.6~0.8% of the mass of cementitious material, and the mass content of water reducer is 0.5~2.0% of the mass of cementitious material.
[0006] Carbon material is an excellent microwave absorbing filler. However, currently commonly used carbon-based additives such as graphite, graphene, and carbon materials disclosed in the above patents have poor dispersibility in cement materials and are difficult to mix evenly with other components of concrete. Therefore, the dosage is limited and the improvement of electromagnetic shielding performance is hindered. In addition, its high price makes it difficult to control the production cost of existing electromagnetic shielding concrete design solutions. Therefore, it is urgent to find low-cost carbon materials with electromagnetic shielding effectiveness, and to develop electromagnetic shielding concrete technical solutions that can effectively solve its compatibility problems in cement materials, so as to break through the bottleneck problem of the development of existing electromagnetic shielding concrete. Summary of the invention
[0007] The invention provides an electromagnetic shielding concrete, which has higher microwave absorption performance and strength.
[0008] The present invention provides an electromagnetic shielding concrete, which is composed of the following raw materials in parts by mass: 100-150 parts of ordinary Portland cement, 54-275 parts of gravel, 90-115 parts of sand, 50-275 parts of microwave absorbing artificial aggregate, 25-35 parts of water and 0.5-1 part of polycarboxylate high-efficiency water reducing agent;
[0009] The microwave absorbing artificial aggregate is obtained by mixing coal gasification fine slag, coal gasification coarse slag and carbide slag, and then subjecting them to standard curing, crushing and hydrothermal curing.
[0010] Compared with the prior art that adds carbon nanotubes, carbon fibers, etc., which are easy to cause segregation and have high costs, the present invention uses artificial aggregates formed by coal gasification slag, which is low in cost, and carbon and other elements are dissolved in the artificial aggregate, which is not easy to precipitate and segregate. While maintaining strength, it can also achieve better electromagnetic shielding.
[0011] Preferably, the stone is 54-110 parts and the microwave absorbing artificial aggregate is 164-218 parts. Appropriate stone parts and microwave absorbing artificial aggregate parts can obtain higher electromagnetic shielding performance under acceptable compressive strength conditions.
[0012] Further preferably, the electromagnetic shielding concrete has a compressive strength of 30-35 MPa, an electromagnetic shielding effectiveness of 26-39 dB at 600 MHz, and an electromagnetic shielding effectiveness of 33-48 dB at 1 GHz.
[0013] Preferably, the microwave absorbing artificial aggregate is microwave absorbing artificial fine aggregate and microwave absorbing artificial coarse aggregate, the particle size of the microwave absorbing artificial fine aggregate is 2.36-4.75 mm (excluding 4.75 mm), and the particle size of the microwave absorbing artificial coarse aggregate is 4.75-20 mm (including 4.75 mm).
[0014] Further preferably, the microwave absorbing artificial fine aggregate is 25-200 parts, and the microwave absorbing artificial coarse aggregate is 15-140 parts.
[0015] By controlling the particle size and the number of microwave absorbing artificial fine aggregate and microwave absorbing artificial coarse aggregate, the microwave absorbing artificial aggregate filling is made updated, dense and uniform, which is beneficial to the uniform distribution of dissolved carbon in concrete and improves the electromagnetic shielding performance.
[0016] Further preferably, the microwave absorbing artificial fine aggregate is 73-110 parts, the microwave absorbing artificial coarse aggregate is 136-145 parts, and the stone is 54 parts. By adjusting the fractions of fine aggregate and coarse aggregate, extremely high electromagnetic shielding performance can be obtained at a lower stone fraction.
[0017] Preferably, the electromagnetic shielding concrete has a compressive strength of 30-38.3 MPa, an electromagnetic shielding effectiveness of 11-39 dB at 600 MHz, and an electromagnetic shielding effectiveness of 19-48 dB at 1 GHz.
[0018] Further preferably, the electromagnetic shielding concrete has a compressive strength of 30-33 MPa, an electromagnetic shielding effectiveness of 34-39 dB at 600 MHz, and an electromagnetic shielding effectiveness of 43-48 dB at 1 GHz.
[0019] Preferably, the hydrothermal reaction temperature of the hydrothermal curing is set at 180-210°C, the heating time of the hydrothermal kettle is 90-120 min, the heating time is 630-720 min, and the cooling time is 360-480 min.
[0020] The present invention uses hydrothermal reaction to react silicon and aluminum in coal gasification fine slag with Ca(OH)2 in alkaline carbide slag to form gel, and the high content of carbon in the coal gasification fine slag is dissolved in the gel to avoid carbon segregation, so that the aggregate has better wave absorbing performance. At the same time, adding coal gasification coarse slag can avoid excessive carbon content causing loose aggregate and causing significant strength reduction.
[0021] Preferably, the coal gasification fine slag, coal gasification coarse slag and carbide slag are mixed with a silicon-calcium ratio of 0.8-1.4 and a residual carbon content of 10-20wt%.
[0022] Preferably, the strength grade of ordinary Portland cement is 42.5 and above.
[0023] Preferably, the stone particle size is selected to be 2.36-15 mm, and the sand is machine-made sand (medium sand) with a particle size of 0.25-0.5 mm.
[0024] Preferably, the preparation method of the artificial microwave absorbing aggregate is: selecting low-cost industrial solid waste coal gasification coarse slag, coal gasification fine slag and carbide slag as raw materials and mixing them in a specific proportion, and preparing them through a process of stirring-injection molding-pre-curing-crushing-hydrothermal curing and the like.
[0025] Preferably, the crude coal gasification slag is rich in aluminosilicate precursors, the carbide slag is rich in alkaline Ca(OH)2, and the fine coal gasification slag contains abundant partially graphitized carbon residues and has good electrical conductivity, and can be used to prepare artificial aggregates with microwave absorption.
[0026] Preferably, the crushing process uses a natural stone crusher to crush the pre-cured and initially hardened whole piece into particles with a continuous particle size distribution, and obtain artificial coarse aggregate with a particle size of 4.75-20 mm and artificial fine aggregate with a particle size of 2.36-4.75 mm by screening.
[0027] Another aspect of the present invention is to provide a method for preparing the electromagnetic shielding concrete, the preparation method comprising:
[0028] S1 Weighing of dry materials: Weigh the following concrete raw materials according to mass proportions: 100-150 parts of ordinary Portland cement, 0-275 parts of gravel, 90-115 parts of sand, 50-275 parts of microwave absorbing artificial aggregate, 25-35 parts of water, and 0.5-1 part of polycarboxylate high-efficiency water reducing agent;
[0029] S2 Dry material mixing: ordinary Portland cement, gravel, sand, microwave absorbing artificial aggregate and all dry materials should be mixed evenly;
[0030] S3 concrete preparation: The polycarboxylate high-efficiency water reducer is first mixed with the mixing water, and then poured into the mixed dry material, and stirred and mixed evenly at a speed of 300-500 r / min to obtain the electromagnetic shielding concrete.
[0031] By adopting the above technical solution, the replacement rate of microwave absorbing artificial aggregate for stone is controlled, which helps to introduce more electromagnetic shielding components on the basis of ensuring the mechanical properties of concrete, better exert the electromagnetic shielding function, and improve the electromagnetic shielding effect.
[0032] Compared with the prior art, the present invention has the following beneficial effects:
[0033] The electromagnetic shielding concrete provided by the present invention has excellent mechanical properties. The electromagnetic shielding component replaces the original component stone in the form of microwave absorbing artificial aggregate, which effectively solves the problem of difficult dispersion and low dosage of carbon materials in concrete, and significantly improves the electromagnetic shielding performance of concrete. On the other hand, the use of microwave absorbing artificial aggregate prepared from industrial solid waste reduces the consumption of natural stone. At the same time, the recycling of solid waste residual carbon has obvious cost advantages and low carbon characteristics compared with conventional electromagnetic shielding components such as graphite and carbon fiber. The electromagnetic shielding concrete of the present invention can meet the long-term use requirements of places that need electromagnetic shielding treatment, such as civil buildings, communication facilities, and military projects. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] Figure 1 It is a schematic flow chart of a method for preparing electromagnetic shielding concrete provided by a specific embodiment of the present invention. DETAILED DESCRIPTION
[0035] The technical solutions in the embodiments of the present invention will be described clearly and completely below in combination with the embodiments of the present invention. It should be pointed out that the described embodiments are only a part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0036] Embodiment 1:
[0037] The electromagnetic shielding concrete of this embodiment is composed of the following raw materials in parts by mass: 100 parts of 42.5 grade ordinary Portland cement, 220 parts of gravel, 110 parts of sand, 30 parts of microwave absorbing artificial coarse aggregate, 30 parts of microwave absorbing artificial fine aggregate, 30 parts of water, and 0.5 parts of polycarboxylic acid high-efficiency water reducing agent.
[0038] The specific preparation method of the microwave absorbing artificial coarse and fine aggregates is as follows: Figure 1 As shown: Industrial solid waste gasification coarse slag, gasification fine slag and carbide slag are selected as raw materials, and the ratio is calculated according to the calcium-silicon atomic ratio of 1.2 and the residual carbon content of 10% and mixed evenly, and prepared through the process flow of stirring-injection molding-pre-curing (sealed pre-curing at 20℃ for 48h)-crushing-hydrothermal curing-drying.
[0039] The specific implementation steps of the stirring process are: mixing the uniformly mixed dry powder with deionized water in a ratio of 1.0:0.4, and fully stirring for 5 minutes under the action of a stirrer with a speed of 500 r / min to obtain a fresh slurry.
[0040] The specific implementation steps of the injection molding process are: immediately injecting the fresh slurry obtained by stirring into a plastic mold of 100 mm×100 mm×100 mm, and shaking it appropriately to reduce bubbles and filler pores inside the specimen.
[0041] The specific implementation steps of the pre-curing process are: use a plastic film to seal the mold to reduce water evaporation, and place the molded slurry under standard curing conditions (temperature 20±2°C, relative humidity ≥95%) for 48 hours before demolding and waiting for the subsequent crushing step.
[0042] The crushing process uses a natural stone crusher to crush the pre-cured and initially hardened whole piece into particles with a continuous particle size distribution, and obtains artificial coarse aggregate with a particle size of 4.75-20 mm and artificial fine aggregate with a particle size of 2.36-4.75 mm through screening.
[0043] The specific implementation steps of the hydrothermal curing process are: the hydrothermal reaction temperature is set to 180°C, the heating time of the hydrothermal kettle is 90 min, the heating time is 630 min, and the cooling time is 360 min.
[0044] The specific implementation steps of the drying process are: the drying equipment uses a blast drying oven, the drying temperature is 60°C, the drying time is 6 hours, and the finished aggregate is obtained after drying.
[0045] The preparation method of electromagnetic shielding concrete in this embodiment is simple and efficient to operate. Figure 1 As shown, specifically:
[0046] S1 Weighing of dry materials: Weigh the following concrete raw materials according to mass proportions: 100 parts of 42.5 grade ordinary Portland cement, 220 parts of gravel, 110 parts of sand, 30 parts of microwave absorbing artificial coarse aggregate, 30 parts of microwave absorbing artificial fine aggregate, 30 parts of water, and 0.5 parts of polycarboxylate high-efficiency water reducing agent.
[0047] S2 Dry material mixing: ordinary Portland cement, gravel, sand, microwave absorbing artificial aggregate and all dry materials should be mixed evenly.
[0048] S3 concrete preparation: The polycarboxylate high-efficiency water reducer is first mixed with mixing water, then poured into the mixed dry material, stirred and mixed at a speed of 300-500 r / min, uniformly introduced into the mold, and cured at 20°C and 95% relative humidity to obtain the electromagnetic shielding concrete.
[0049] Embodiment 2:
[0050] This embodiment is different from Example 1 in that the electromagnetic shielding concrete of this embodiment is composed of the following raw materials in parts by mass: 100 parts of 42.5 grade ordinary Portland cement, 220 parts of gravel, 110 parts of sand, 18 parts of microwave absorbing artificial coarse aggregate, 36 parts of microwave absorbing artificial fine aggregate, 30 parts of water, and 0.5 parts of polycarboxylic acid high-efficiency water reducing agent, and the rest are consistent with Example 1.
[0051] Embodiment 3:
[0052] This embodiment is different from Embodiment 1 in that the electromagnetic shielding concrete of this embodiment is composed of the following raw materials in parts by mass: 100 parts of 42.5 grade ordinary Portland cement, 160 parts of gravel, 110 parts of sand, 55 parts of microwave absorbing artificial coarse aggregate, 55 parts of microwave absorbing artificial fine aggregate, 30 parts of water, and 0.5 parts of polycarboxylic acid high-efficiency water reducing agent, and the rest are consistent with Embodiment 1.
[0053] Embodiment 4:
[0054] This embodiment is different from Example 1 in that the electromagnetic shielding concrete of this embodiment is composed of the following raw materials in parts by mass: 100 parts of 42.5 grade ordinary Portland cement, 160 parts of gravel, 110 parts of sand, 36 parts of microwave absorbing artificial coarse aggregate, 73 parts of microwave absorbing artificial fine aggregate, 30 parts of water, and 0.5 parts of polycarboxylic acid high-efficiency water reducing agent, and the rest are consistent with Example 1.
[0055] Embodiment 5:
[0056] This embodiment is different from Example 1 in that the electromagnetic shielding concrete of this embodiment is composed of the following raw materials in parts by mass: 100 parts of 42.5 grade ordinary Portland cement, 110 parts of gravel, 110 parts of sand, 82 parts of microwave absorbing artificial coarse aggregate, 82 parts of microwave absorbing artificial fine aggregate, 30 parts of water, and 0.5 parts of polycarboxylic acid high-efficiency water reducing agent. The rest are consistent with Example 1.
[0057] Embodiment 6:
[0058] This embodiment is different from Embodiment 1 in that the electromagnetic shielding concrete of this embodiment is composed of the following raw materials in parts by mass: 100 parts of 42.5 grade ordinary Portland cement, 110 parts of gravel, 110 parts of sand, 54 parts of microwave absorbing artificial coarse aggregate, 110 parts of microwave absorbing artificial fine aggregate, 30 parts of water, and 0.5 parts of polycarboxylic acid high-efficiency water reducing agent, and the rest are consistent with Embodiment 1.
[0059] Embodiment 7:
[0060] This embodiment is different from Example 1 in that the electromagnetic shielding concrete of this embodiment is composed of the following raw materials in parts by mass: 100 parts of 42.5 grade ordinary Portland cement, 54 parts of gravel, 110 parts of sand, 110 parts of microwave absorbing artificial coarse aggregate, 110 parts of microwave absorbing artificial fine aggregate, 30 parts of water, and 0.5 parts of polycarboxylic acid high-efficiency water reducing agent, and the rest are consistent with Example 1.
[0061] Embodiment 8:
[0062] This embodiment is different from Example 1 in that the electromagnetic shielding concrete of this embodiment is composed of the following raw materials in parts by mass: 100 parts of 42.5 grade ordinary Portland cement, 54 parts of gravel, 110 parts of sand, 73 parts of microwave absorbing artificial coarse aggregate, 145 parts of microwave absorbing artificial fine aggregate, 30 parts of water, and 0.5 parts of polycarboxylic acid high-efficiency water reducing agent, and the rest are consistent with Example 1.
[0063] Comparative Example 1:
[0064] The difference between this comparative example and Example 1 is that the ordinary concrete of this example is composed of the following raw materials in parts by mass: 100 parts of 42.5 grade ordinary Portland cement, 110 parts of sand, 136 parts of microwave absorbing artificial coarse aggregate, 136 parts of microwave absorbing artificial fine aggregate, 30 parts of water, and 0.5 parts of polycarboxylate high-efficiency water reducing agent, and the rest are consistent with Example 1.
[0065] Comparative Example 2
[0066] This comparative example is different from Example 1 in that the ordinary concrete of this example is composed of the following raw materials in parts by mass: 100 parts of 42.5 grade ordinary Portland cement, 110 parts of sand, 91 parts of microwave absorbing artificial coarse aggregate, 181 parts of microwave absorbing artificial fine aggregate, 30 parts of water, and 0.5 parts of polycarboxylate high-efficiency water reducing agent, and the rest are consistent with Example 1.
[0067] Comparative Example 3:
[0068] The difference between this comparative example and Example 1 is that the ordinary concrete of this example is composed of the following raw materials in parts by mass: 100 parts of 42.5 grade ordinary Portland cement, 272 parts of gravel, 110 parts of sand, 30 parts of water, and 0.5 parts of polycarboxylic acid high-efficiency water reducing agent, and the rest are consistent with Example 1.
[0069] The concrete samples of Examples 1 to 8 and Comparative Examples 1 to 3 were subjected to performance tests, including:
[0070] Compressive strength test: Referring to the Standard Test Methods for Mechanical Properties of Ordinary Concrete (GB / T 50081), the concrete samples were made into several standard blocks with a side length of 100 mm. The compressive strength test was carried out after curing for 28 days under standard curing conditions of 20°C and 95% relative humidity.
[0071] Electromagnetic shielding effectiveness test: The electromagnetic shielding concrete and ordinary concrete samples were prepared into 3.6 mm specimens. The electromagnetic shielding transmission coefficient curves of the samples in the range of 600 MHz to 1 GHz were scanned using an impedance analyzer to obtain the electromagnetic shielding effectiveness at 600 MHz and 1 GHz.
[0072] The performance results are shown in Table 1:
[0073] Table 1 Compressive strength and electromagnetic shielding effectiveness of concrete in the examples and comparative examples
[0074]
[0075] In Comparative Example 3, no microwave absorbing artificial aggregate is added, and the prepared concrete product has low electromagnetic shielding efficiency and poor electromagnetic shielding effect, which cannot meet the use requirements of places requiring electromagnetic shielding treatment.
[0076] Comprehensive analysis of Examples 1 to 8 and Comparative Examples 1 and 2 shows that, in the process of preparing electromagnetic shielding concrete, microwave absorbing artificial aggregate is added, and the electromagnetic shielding effectiveness of the prepared electromagnetic shielding concrete product is significantly improved. This improvement effect increases with the increase in the amount of microwave absorbing artificial aggregate replacing stone. But on the contrary, with the reduction of stone, the compressive strength of electromagnetic shielding concrete also decreases. Comprehensively evaluating the compressive strength and electromagnetic shielding effectiveness of electromagnetic shielding concrete, it is believed that the amount of microwave absorbing artificial aggregate replacing stone described in Example 8 has reached the maximum limit of electromagnetic shielding concrete. If this limit is exceeded, the compressive strength is less than 30 MPa, which cannot meet the requirements of actual engineering for the mechanical properties of concrete.
[0077] Comparing the experimental results of Example 7 and Example 8, the mass ratios of the microwave absorbing artificial coarse aggregate and the microwave absorbing artificial fine aggregate used in the two examples are different, and the effects on the compressive strength and microwave absorption efficiency are also different. By comparing the results, it is believed that when the ratio between the microwave absorbing coarse aggregate and the fine aggregate is controlled at 1:1, the compressive strength and electromagnetic shielding efficiency of the electromagnetic shielding concrete are both good.
[0078] The above shows and describes the basic principles, main features and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited to the above embodiments, and various changes, modifications, substitutions and variations can be made to these embodiments without departing from the principles and spirit of the present invention. The scope of the present invention is defined by the attached claims and their equivalents.
Claims
1. An electromagnetic shielding concrete, characterized in that: The electromagnetic shielding concrete is composed of the following raw materials in parts by mass: 100-150 parts of ordinary Portland cement, 54-275 parts of gravel, 90-115 parts of sand, 50-275 parts of microwave absorbing artificial aggregate, 25-35 parts of water and 0.5-1 part of polycarboxylate high-efficiency water reducing agent; The microwave absorbing artificial aggregate is obtained by mixing coal gasification fine slag, coal gasification coarse slag and carbide slag, stirring, injection molding, standard curing, crushing and hydrothermal curing, wherein the stirring process is to stir the mixed dry powder with deionized water.
2. The electromagnetic shielding concrete according to claim 1, characterized in that: The stone comprises 54-110 parts and the microwave absorbing artificial aggregate comprises 164-218 parts.
3. The electromagnetic shielding concrete according to claim 2, characterized in that: The electromagnetic shielding concrete has a compressive strength of 30-35 MPa, an electromagnetic shielding effectiveness of 26-39 dB at 600 MHz, and an electromagnetic shielding effectiveness of 33-48 dB at 1 GHz.
4. The electromagnetic shielding concrete according to claim 1, characterized in that: The microwave absorbing artificial aggregate includes microwave absorbing artificial fine aggregate and microwave absorbing artificial coarse aggregate. The particle size of the microwave absorbing artificial fine aggregate is 2.36-4.75 mm, and the particle size of the microwave absorbing artificial coarse aggregate is 4.75-20 mm.
5. The electromagnetic shielding concrete according to claim 4, characterized in that: The microwave absorbing artificial fine aggregate is 25-200 parts, and the microwave absorbing artificial coarse aggregate is 15-140 parts.
6. The electromagnetic shielding concrete according to claim 4, characterized in that: The microwave absorbing artificial fine aggregate accounts for 73-110 parts, the microwave absorbing artificial coarse aggregate accounts for 136-145 parts, and the gravel accounts for 54 parts.
7. The electromagnetic shielding concrete according to claim 6, characterized in that: The electromagnetic shielding concrete has a compressive strength of 30-33 MPa, an electromagnetic shielding effectiveness of 34-39 dB at 600 MHz, and an electromagnetic shielding effectiveness of 43-48 dB at 1 GHz.
8. The electromagnetic shielding concrete according to claim 1, characterized in that: The hydrothermal reaction temperature of the hydrothermal curing is 180-210°C, the heating time of the hydrothermal kettle is 90-120 min, the heating time is 630-720 min, and the cooling time is 360-480 min.
9. The electromagnetic shielding concrete according to claim 1, characterized in that: The coal gasification fine slag, coal gasification coarse slag and carbide slag are mixed with a silicon-calcium ratio of 0.8-1.4 and a residual carbon content of 10-20 wt%.
10. A method for preparing electromagnetic shielding concrete according to any one of claims 1 to 9, characterized in that: include: S1 dry material mixing: weighing raw materials according to the mass fraction of the electromagnetic shielding concrete according to any one of claims 1 to 9, and mixing them evenly to obtain a mixed dry material; S2 concrete preparation: The polycarboxylate high-efficiency water reducer is first mixed with mixing water, and then poured into the mixed dry material, and stirred and mixed evenly at a speed of 300-500 r / min to obtain the electromagnetic shielding concrete.
